A discourse on foresight and the valuation of explicit and tacit synergies in strategic collaborations - Andrejs Čirjevskis (Journal of Risk and Financial Management, 2022)
One of the most important questions in business partners' collaboration is whether their strategies create a collaborative synergy and thus add market value. This paper aims to develop a conceptual framework that will be useful for scholars and practitioners in developing foresight for explicit synergies and valuing tacit synergy in strategic collaborative ventures. The paper comprises a novel theoretical and empirical contribution to the foresight that is required for an explicit competence-based synergy in collaborative ventures from a resource-based view. It employs the ARCTIC framework and values a tacit competence-based synergy using simple and compound real options. Moreover, the paper makes several theoretical and empirical contributions to the study of strategic management, international business, and corporate finance disciplines. Finally, the paper discusses research limitations and future work.
Keywords: 650; collaborative ventures; core competence; explicit synergy; real options; tacit synergy; the ARCTIC framework